Role of endomyocardial biopsy guided by electroanatomic voltage mapping for the diagnosis of cardiomyopathies in patients with arrhythmic presentation. (25th November 2020) - Bergonti, M; Dello Russo, A; Gasperetti, A; Catto, V; Vettor, G; Sicuso, R; Ribatti, V; Carbucicchio, C; Di Biase, L; Sommariva, E; Andreini, D; Basso, C; et al.
Abstract: Background: A myocardial substrate assessment through percutaneous endomyocardial biopsy (EMB) represents an important additional diagnostic test for cardiomyopathies when uncertainties remain after non-invasive evaluation. Yet, extensive application of EMB has been limited by the low sensitivity of biopsies. Electroanatomic voltage mapping (EVM) is a promising modality for guiding Endomyocardial biopsies (EMB). Aim: The aim of our study is to evaluate the diagnostic yield of EVM-guided EMB and the role of histological analysis in the diagnosis of patients with suspected cardiomyopathies and arrhythmic presentation. Methods: One-hundred and sixty-two consecutive patients undergoing EMB at our Institution from 2010 to 2019 were included. Demographics, clinical data, CMR data and peri-procedural complications were retrospectively retrieved. All procedures were guided by endo-cavitary EVM. According to non-invasive data collected before proceeding with EMB a suspected clinical diagnosis was expressed and compared to histological diagnosis Results: One-hundred and sixty-two patients were included in the study. Mean age of the cohort resulted 40.9±14.7 years, with 26.5% of the included patients being females. ECG alterations were present in 51.3% of the population, with the most common abnormality being T wave inversion. Sustained or non-sustained ventricular tachycardia was registered in 51 (31.5%) of the patients, while 44 (27.2%) patients were referred for frequent isolated premature ventricular complex (PVC), and 19 (11.7%) after an episode of an arrhythmogenic syncope or resuscitated cardiac arrest. Suspected ARVC (41.6%) together with acute/chronic myocarditis (28.0%) were the main clinical diagnosis leading to an invasive approach. The sampling site was the right ventricle in 116 (72.5%), the left ventricle in 31 (19.4%), and both ventricles in 13 (8.1%) patients. Biopsy samplings were judged appropriate for histological analysis in 141 (87.0%) patients. Among the analyzed samples, a diagnosis was reached in 120 patients (74.1%). In the remaining 21 cases (25.9%), the analysis yielded nonspecific histologic findings, inconclusive results, or sampling error. The biopsy allowed to confirm the clinical diagnosis in 72 (60.0%) patients, while a different diagnosis was reached in 48 (39.0%) cases (Reclassification are showed Figure 1).In particular of 67 (41.6%) patients suspected for ARVC, only 32 (22.7) reached a confirmation. Conversely, the number of patients with acute/chronic myocarditis augmented from 45 (28.0%) to 47 (33.3%). Conclusion: EMB guided by EVM reached a diagnostic yield as high as 74.1%. EMB proved to be a useful tool in the clinical management of patients, as it allowed to correctly reclassify a significant number of patients who would have been misdiagnosed based only on non-invasive assessment. Funding Acknowledgement: Type of funding source: None